One Health conceptualization of sustainable diets looking at low- and middle-income settings: a systematic literature review - Edith Monica Esievo; Edith Monica Esievo; Edith Monica Esievo; Edith Monica Esievo; Louise Whatford; Sarah Nájera Espinosa; Oche Abraham Awulu; Oche Abraham Awulu; Aliyu Nuhu Ahmed; Kris A. Murray; Zakari Ali (Frontiers in Sustainable Food Systems)
Unhealthy diets are proven risks for non-communicable diseases and mortality globally. Low- and Middle-Income Countries (LMICs) are equally faced with food/nutrition insecurity, poor health outcomes, and the need for sustainable food systems transformation to cater for the growing population within safe planetary boundaries. Despite significant progress globally, persistent challenges necessitate a more holistic and systemic approach to healthy sustainable diets, particularly in LMICs which are often underrepresented in global studies. This review conceptualizes sustainable diets looking at LMICs by assessing sustainability through the One Health approach which considers the interdependencies among humans, animals, plants, and the environment. Using the preferred reporting items of systematic reviews and meta-analyses (PRISMA) guidelines and the checklist for One Health epidemiological reporting of evidence (COHERE) standards, four databases were searched (Embase, Global Health, Web of Science, and Scopus) between 1947 and June 2023. Dietary sustainability was assessed in LMICs by evaluating coverage across the four One Health pillars (human, animal, plant, and environmental health) and five dietary sustainability dimensions (diet/nutrition, health, environment, economic, and social). Extracted data were analyzed qualitatively. The database searches yielded 3,122 studies. After removing duplicates and screening for eligibility, 35 studies were selected for inclusion. Most studies were from upper (77%) and lower (20%) middle-income countries. While 20 studies (57%) assessed human and environmental health, none assessed plant or animal health, nor all four One Health pillars combined. No study assessed all five dietary sustainability dimensions. Most studies assessed two (54%) or three (34%) dimensions, and the most frequently assessed dimension was the environment (71%). Thus, highlighting the non-comprehensive nature and the dearth of research on sustainable diets conducted in LMICs, particularly, low-income countries, and that the research so far mainly focuses on environmental impacts. Overall, studies found that LMICs’ diets, particularly middle-income countries, are unsustainable due to low quality, low diversity, and high environmental effects, with associated inequities. The underrepresentation of LMICs, particularly low-income countries, in this review is a wake-up call urging the generation of more country-specific data incorporating more dietary sustainability dimensions and One Health pillars (especially plant and animal health) for progress and monitoring toward attaining global dietary sustainability.